Erythrocyte Membrane Fluidity Alterations in Sudden Sensorineural Hearing Loss Patients: The Role of Oxidative Stress - Becatti, Matteo; Marcucci, Rossella; Mannucci, Amanda; Gori, Anna Maria; Giusti, Betti; Sofi, Francesco; Mannini, Lucia; Cellai, Anna Paola; Alessandrello Liotta, Agatina; Mugnaini, Marco; Emmi, Giacomo; Prisco, Domenico; Taddei, Niccolò; Fiorillo, Claudia (Thrombosis and Haemostasis, 2017)
Introduction Sudden sensorineural hearing loss (SSNHL) involves an acute unexplained hearing loss, nearly always unilateral, that occurs over less than a 72-hour period. SSNHL pathogenesis is not yet fully understood. Cochlear vascular occlusion has been proposed as a potential mechanism of hearing damage and cochlear ischaemia has been related to alterations of cochlear microvessels. In addition, some researchers have focused their attention on the rheological alterations and blood hyperviscosity. Erythrocyte deformability plays a key role in determining blood viscosity, and it is critical to cochlear perfusion. It has been shown that oxidative stress-induced erythrocyte membrane fluidity alterations are linked to the progression of cardiovascular diseases.Methods To determine whether erythrocytes from SSNHL patients show signs of oxidative stress, and whether this condition can modify the haemorheologic profile in these patients, we analysed haemorheologic profile and erythrocyte oxidative stress in 35 SSNHL patients and 35 healthy subjects, matched for age and sex. Fluorescence anisotropy was used to evaluate the fluidity of erythrocyte membranes.Results Our results show a significant structural and functional involvement of erythrocyte membrane alterations in SSNHL, as well as elevated levels of membrane lipid peroxidation and intracellular reactive oxygen species (ROS) production. In addition, erythrocyte-derived ROS and erythrocyte lipid peroxidation positively correlated with whole blood viscosity and erythrocyte deformability. Moreover, in vitro experiments demonstrated that ROS display a key role in erythrocyte membrane fluidity.Conclusion These findings indicate that erythrocyte oxidative stress plays a key role in the pathogenesis of SSNHL and pave the way to new therapeutic interventions.
Keywords: blood viscosity; erythrocyte deformability; erythrocyte membrane; oxidative stress; sudden sensorineural hearing loss